MICRO-CREDENTIALS FOR PROFESSIONAL DEVELOPMENT OF TEACHERS: EXPERIENCE OF OPEN UNIVERSITY (UK) - Olena Myroshnichenko (Borys Grinchenko Kyiv Metropolitan University, 2024)
The article is devoted to the justification of the role of micro-credentials in the professional development of teachers on the example of the Open University (UK). It was emphasized that the introduction of micro-credentials is a modern trend in the European area of higher education. The absence of a generally accepted definition of micro-credentials is accentuated; both their advantages over traditional systems of professional development of teachers and the disadvantages of their implementation are emphasized. It was found that the growth in the number and role of micro-credentials s in the UK and the lack of a generally accepted understanding led the Quality Assurance Agency to outline the necessary characteristics of micro-credentials: clearly defined admission and access requirements (including recognition of prior learning); course design, including training, teaching, assessment and certification; learning outcomes and skills; course certification; standard quality assurance mechanisms. It has been determined that micro-credentials are based on content studied at a «microlevel», i.e. independent, but smaller than a degree qualification. It has been determined that micro-credentials are based on content studied at a «microlevel», in other words independent, but smaller than a degree qualification. The experience of the Open University in introducing micro-credentials for the professional development of teachers was analyzed using the example of the microcredit «Mentoring and coaching in professional training». It is noted that the Open University promotes a flexible, inclusive, adaptive, accessible education system that relies on the independence and autonomy of those who study, and micro-credentials allow students to acquire practical skills that correspond to their career aspirations and personal interests, without receiving a full educational degree.